Effect of MAG welding transfer mode on sigma phase precipitation and corrosion performance of 316L stainless steel multi-pass welds - L.H. Guilherme; A.V. Benedetti; C.S. Fugivara; R. Magnabosco; M.F. Oliveira (Journal of Materials Research and Technology, 2020)
The effect of multi-pass MAG welding transfer modes on the sigma phase precipitation and corrosion performance of AISI 316L thick plate were investigated. The evolution of the microstructure was examined by optical and electron microscopy as well as ferritscope measurements and energy dispersive X-ray spectrometry. An electrochemical microcell was then used to characterize the electrochemical behaviour of the different weld regions. The fusion line was the most critical zone for pitting corrosion for all welding procedures, due to the sigma phase precipitation, alloy elements partitioning and galvanic coupling between base metal and weld metal. It was observed the formation of sigma phase after short-circuiting or spray-arc modes, with no evidence of it to the pulsed-arc, which obtained the best corrosion resistance performance. The results evidenced the selective corrosion around sigma phase due to the depletion in Cr and Mo, with subsequent pitting nucleation. A strong correlation between the MAG welding transfer modes and the sigma phase morphology was observed. The influence of weld parameters on microstructure evolution and corrosion resistance performance was discussed. The corrosion resistance performance of the MAG welding procedures was ranked as: pulsed-arc > short-circuit > spray-arc.